2017
DOI: 10.5539/jas.v9n2p53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acacia angustissima Leaf Meal on the Physiology of Broiler Intestines

Abstract: The effect of A. angustissima leaf meal based diets on intestinal physiology and dressed carcass weight was investigated on 150 day old chicks. Three diets, 0, 5 and 10% A. angustissima were used in a three phase feeding programme. At days 14, 28 and 42, two birds from each replicate were slaughtered, dressed and weighed. The weights and lengths of the duodenum, jejunum and colon were measured. Approximately 1 cm specimen was taken from each organ, fixed in formalin and stained for histological analysis. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…For example, Tessema and Baars (2006) found values of NDF (46.50%) and ADF (35.4%) in Desmodium uncinatum, which are lower than those reported in this study (Table 2). For the Ash variable, Ncube et al (2017) found values of 4.3% in Acacia angustissima, and Ojo et al (2012) found values of 5.3% in Tephrosia bracteolata, similar to those in this study (Table 3). Ojo et al (2012) reported 13.6% of CL and 2.2% of EE in Tephrosia bracteolata.…”
Section: Resultssupporting
confidence: 89%
“…For example, Tessema and Baars (2006) found values of NDF (46.50%) and ADF (35.4%) in Desmodium uncinatum, which are lower than those reported in this study (Table 2). For the Ash variable, Ncube et al (2017) found values of 4.3% in Acacia angustissima, and Ojo et al (2012) found values of 5.3% in Tephrosia bracteolata, similar to those in this study (Table 3). Ojo et al (2012) reported 13.6% of CL and 2.2% of EE in Tephrosia bracteolata.…”
Section: Resultssupporting
confidence: 89%
“…This represents an enhanced development of the intestinal segment [28][29]. An increase in the intestinal length could also result from an increase in gastro-duodenal refluxes as triggered by the high fiber content in the leaf meal feed base diet [29][30][31]. In this study, chicken fed with more than 5% AMLM diet tended to have higher gizzard wall thickness.…”
Section: Carcass Compositionmentioning
confidence: 73%
“…The increase in the size of the intestinal segments is a physical adaptation to the presence of the AMLM. This represents an enhanced development of the intestinal segment [28][29]. An increase in the intestinal length could also result from an increase in gastro-duodenal refluxes as triggered by the high fiber content in the leaf meal feed base diet [29][30][31].…”
Section: Carcass Compositionmentioning
confidence: 99%
“…Stage of harvesting is noted to significantly affect the deposition of plant cell wall (NDF and ADF). The vegetative growth phase of plants is usually characterised by lower NDF and ADF fraction with higher CP concentration than the reproductive or flowering growth phase [ 21 ]. The differences in NDF and ADF in the present study is an indication that the deposition of structural carbohydrates in cowpea haulms can be influenced by V and P doses even though they were all harvested at the same growth stage.…”
Section: Discussionmentioning
confidence: 99%